2020
DOI: 10.1002/aur.2411
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Maternal Immune Activation and Antibiotic Use during Pregnancy and Child Risk of Autism Spectrum Disorder

Abstract: Prenatal exposure to maternal immune activation (MIA) has been implicated as a risk factor for the development of autism spectrum disorder (ASD), though the conditions under which this elevated risk occurs are unclear. Animal literature demonstrates that antibiotic use, which affects the composition of the maternal gut microbiota, modifies the effect of MIA on neurodevelopmental outcomes in the offspring. The aim of this study was to assess whether antibiotic use during pregnancy modifies the association betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 62 publications
0
20
0
Order By: Relevance
“…Notably, in contrast to all the other results in this study, systemic antifungal medications were associated with an increased risk of ASD. While this association may be due to the severity of the infection rather than to the iatrogenic effects of the prescribed antimicrobials (49,50), this finding should be regarded with caution since only 15 women (0.6%) in our sample were prescribed this medication.…”
Section: Discussionmentioning
confidence: 74%
“…Notably, in contrast to all the other results in this study, systemic antifungal medications were associated with an increased risk of ASD. While this association may be due to the severity of the infection rather than to the iatrogenic effects of the prescribed antimicrobials (49,50), this finding should be regarded with caution since only 15 women (0.6%) in our sample were prescribed this medication.…”
Section: Discussionmentioning
confidence: 74%
“…The analysis showed an interaction between the effect of flu and antibiotic use during pregnancy on the risk of ASD in the child. In women with antibiotic use during pregnancy, flu in trimester two was not associated with ASD, while in those without antibiotic use, flu in second trimester was significantly associated with increased risk of ASD [89]. The pathophysiological mechanisms underlying this positive association remains elusive but is likely to be two-fold [88].…”
Section: Maternal Cytokines In Asdmentioning
confidence: 98%
“…However, a meta-analysis by Jiang et al, systematically examining 15 studies and 40,000 cases of ASD, concluded that maternal infections during pregnancy, particularly those requiring hospitalisation, do indeed increase the risk of ASD in new-borns [88]. A recent prospective birth cohort study with 116 ASD cases and 860 typically developing (TD) children looked at the effect of antibiotic use on the relationship between immune activation and the ASD risk [89]. The analysis showed an interaction between the effect of flu and antibiotic use during pregnancy on the risk of ASD in the child.…”
Section: Maternal Cytokines In Asdmentioning
confidence: 99%
“…Reports have documented that maternal diet during lactation modulates the composition of breast milk, glucose tolerance, and weight of the infant (7). Also, it had been confirmed that negative physiological conditions such as obesity, overweight, or overnutrition with energy-dense diets are associated with a pro-inflammatory profile and immune activation in the plasma of the infants after birth (114)(115)(116)(117)(118). In humans, 25% of calorie intake in obese people comes from snacks and junk food (119), which could have a negative contribution on breastfeeding composition and health in the newborns from obese mothers.…”
Section: Maternal Diet Modulates Breast Milk-gut Microbiome Interplay and Immunity In The Newbornmentioning
confidence: 97%